Potassium Dynamics Under Exhaustive Cropping of Sudan Grass (Sorghum vulgare) in Some Indian Soils: Potassium Dynamics of Sorghum vulgare (Biological Sciences - PJSIR, 2009)
In order to study the effect of different levels of K exhaustion on potassium dynamics, Sudan grass was grown in clay pots containing 5 kg of three types of soils each namely Alfisol, Vertisol, and Inceptisol from India. Potassium was applied at the rate of 0, 50, 100, and 200 mg/kg before starting the experiment and after each of the first three cuttings. Seven cuts of Sudan grass were taken over a period of 280 days, at 4-6 week intervals. Potassium content of Sudan grass increased with increased amounts of K applied as fertilizer. The highest values for K concentra- tion in Sudan grass were recorded in the 1st and the 2nd cuts and gradually decreased up to the last cut, but the rate of decrease was much lower in moderately exhausted soils (AK200, BK200, and RK200). In Inceptisol and Vertisol as the intensity of exhaustion increased the contribution of non-exchangeable K (NE-K) to meet the plant demand also increased, but in Alfisol a reverse trend was noticed (decrease in replenishment rate). Total amount of NE-K utilized by crop was high in K0 and low in K200 treatment in all the soils, but the proportion of percent share of K0/K200 was the highest in Inceptisol (4.5), medium in Vertisol (3.50) and the lowest in Alfisol (2.29).